200 years since José Gervasio Artigas entered Paraguay (Res Gesta, 2020)
This 2020 marks the two hundredth anniversary of the arrival of José Gervasio Artigas to Paraguay, where he lived for thirty years until his death in 1850. For this reason, the cultural supplement of the newspaper ABC Color invited four historians from Uruguay, Argentina and Paraguay to write about the context and circumstances in which this event took place, and to offer observations that shed light on the three decades that Artigas spent in Paraguay, witnessing profound political and social transformations. During the preparation of the texts, the authors engaged in dialogue, exchanged ideas, read each other and became more aware - if possible - of the need to deepen the conversation. Thus, it seemed appropriate to revise and expand the scope of the contributions and then publish them in the format of an authentic round table for dialogue and exchange of information on exile, social life in nineteenth-century Paraguay and the connections of federalism in Uruguay, Paraguay and Argentina.